Application of the STAD-Type Cooperative Model Assisted by Wordwall to Enhance Students Critical Thinking Ability - Putri, Alivi Lindi; Rahmad, M; Sahal, M (Postgraduate, University of Mataram, 2023)
An advanced nation begins with individuals who are able to compete with other individuals based on the standards of ability needed by the world community, which are known as 21st-century abilities, one of which is the critical thinking ability. The application of the STAD-type cooperative model assisted by Wordwall aims to describe students critical thinking abilities and find differences in critical thinking abilities between control and experiment classes. The research design used nonequivalent post-test only control group. This research included all students in class X of MIPA SMA Muhammadiyah 1 Pekanbaru as a population. A sample of 66 students consisted of X MIPA 1 as control class and X MIPA 5 as experiment class. After the research was carried out, a critical thinking abilities post-test was given, which consisted of 12 multiple-choice questions as an instrument for data collection. Post-test results were analyzed using descriptive analysis and inferential. The results of the descriptive analysis showed that the experiment class was in the very good category with score 80.99, and the control class was in the good category with score 61.03. Then, in the inferential analysis, it is known that there are significant differences between experiment and control class